“Aplicación de las metodologías de observación directa e indirecta en el monitoreo del zorro andino (lycalopex culpaeus reissii), para determinar su presencia en los páramos de la parroquia de Poaló” - Garcés Zúñiga, Dagmar Monserrath (2023)
The Andean fox (Lycalopex culpaeus reissii) inhabits the high equatorial mountains at altitudes ranging between 2600 and 4810 m.s.n.m, occupying areas such as punas, shrublands, and places where there is human presence such as agricultural crops and livestock areas. However, the presence of anthropogenic activities such as agricultural areas, overgrazing, indiscriminate hunting and the entry of exotic fauna cause alterations and fragmentation of the Andean fox's natural habitat, where 58% of the area where it lives is altered. The present research project was developed with the objective of determining the presence of (Lycalopex culpaeus reissii) in the moorlands of the Poaló parish with the application of direct and indirect observation methods. The applied methodological approach consists of two stages; the preparatory stage in which the project was explained to the parish authorities, as well as the introductory practice and the field stage, which included the global positioning, the drawing of five transects in different sectors of Angaguana, taking samples of feces, hair, footprints, skeletal remains, etc. The application of the survey to the local inhabitants. A total of 46 samples were obtained, showing the presence of the Andean fox (Lycalopex culpaeus reissii). In addition, there are indirect human interactions with the fox because the fox's habitat overlaps with human settlements where South American camelid and cattle farms are located, which is why the culpeo has begun to feed on camelid offspring, causing the local people to decide to hunt the fox. On the other hand, the information gathered from the community survey shows that there is no feral fauna in the area.